(untitled) (Revista Paradigma, 2020)
Given the theoretical and dogmatic inconsistencies related to the idea of vulnerability, the present work seeks to understand, describe, explain and justify the information processing methods of the Superior Court of Justice in Brazil, which are useful to collaborate on a rapid recovery, by the user, of the court decisions. These methods include the process of Indexing, the Controlled Legal Vocabulary and the Legal Thesaurus. In order to do so, it aims, through the notion of vulnerability, to map out the criteria for delimiting sample universes within the Court, so that the meanings and related possibilities can be revealed. The research is metascientific, given that jurimetrics, as a scientific method, is also adopted to problematize the structure itself, supported by the use of empiricism. It was possible to identify the terms authorized to the indexing process pertinent to vulnerability, which made it possible to frame the criteria for delimiting the sample universe. The terms found and the size of the delimited universe allowed conclusions that reveal vulnerability as a legal principle, at the same time that engenders its banalization, due to a contingent polysemy. Thus, it becomes clear that the structure of these decision-search tools for jurimetrics is determinant of the findings themselves, which are restricted to a previous semantic understanding that tends to remain invisible.